2015
DOI: 10.1088/1478-3975/12/5/056005
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of wound-induced intercellular Ca2+flashes in a developing epithelium

Abstract: Differential mechanical force distributions are increasingly recognized to provide important feedback into the control of an organ’s final size and shape. As a second messenger that integrates and relays mechanical information to the cell, calcium ions (Ca2+) are a prime candidate for providing important information on both the overall mechanical state of the tissue and resulting behavior at the individual-cell level during development. Still, how the spatiotemporal properties of Ca2+ transients reflect the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 94 publications
(181 reference statements)
8
35
0
Order By: Relevance
“…2G, Movie S5, S6). Additionally, we confirmed several of the components previously implicated in Ca 2+ signaling in the wing disc are required for ICW dynamics through RNAi experiments: ICWs require Ca 2+ release through IP 3 R, Ca 2+ recycle through SERCA and diffusion through gap junctions (9,14,16,30,36) (Movie S7-9). Ca 2+ channels Stim, Orai and PMCA did not qualitatively impact ICWs activity (Movie S10-12).…”
Section: Stimulation Of Icws Requires the Plcβ1 Homolog Plc21csupporting
confidence: 77%
See 2 more Smart Citations
“…2G, Movie S5, S6). Additionally, we confirmed several of the components previously implicated in Ca 2+ signaling in the wing disc are required for ICW dynamics through RNAi experiments: ICWs require Ca 2+ release through IP 3 R, Ca 2+ recycle through SERCA and diffusion through gap junctions (9,14,16,30,36) (Movie S7-9). Ca 2+ channels Stim, Orai and PMCA did not qualitatively impact ICWs activity (Movie S10-12).…”
Section: Stimulation Of Icws Requires the Plcβ1 Homolog Plc21csupporting
confidence: 77%
“…We have shown that ICWs can be stimulated by the release of compression in wing discs (Narciso et al, 2017). Laser ablation of cells leads to rapid dissipation of mechanical stress and Ca 2+ flashes in the wing discs cultured in fly extract-free medium (Narciso et al, 2015). In addition, it was shown that the myosin II inhibitor blebbistatin interrupted Ca 2+ oscillations in the wing disc (Balaji et al, 2017).…”
Section: Suppression Of Hedgehog Signaling Increases Ca 2+ Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…Ca 2+ is a second messenger, and Ca 2+ signaling networks often exhibit a “bow‐tie” structure in that the integrated effect of many inputs is governed by a small number of molecules in the calcium pathway, and they affect many outputs (Brodskiy & Zartman, ), similar to the way that many growth‐affecting factors impinge upon the Hippo kinase cascade. Like Hippo, growth and mechanical signals both affect Ca 2+ (Antunes, Pereira, Cordeiro, Almeida, & Jacinto, ; Balaji et al, ; Brodskiy et al, ; Narciso et al, ; Narciso, Contento, Storey, Hoelzle, & Zartman, ; Restrepo & Basler, ). Ca 2+ signaling in the wing disk exhibits a rich variety of dynamical behaviors.…”
Section: Biochemical Regulation Of Growth and Patterningmentioning
confidence: 99%
“…In embryonic wounds, the NADPH oxidase DUOX, which acts as a source of H 2 O 2 , is activated by calcium, and Ca 2+ flashes have been found upon damage [43]. Intercellular Ca 2+ waves, propagated via gap junctions are triggered by injury to imaginal discs [44, 45]. …”
Section: Wound Healing and Early Responses To Tissue Damagementioning
confidence: 99%